Hot corrosion of TBC‐coated components upon combustion of low‐sulfur fuels - Holländer, Christian; Kiliani, Stefan; Stamm, Werner; Lüsebrink, Oliver; Harders, Harald; Wessel, Egbert; Müller, Michael; Singheiser, Lorenz (Materials and corrosion, 2021)
Gas turbine reliability is a crucial requirement for passenger safety in aviation and a secure energy supply. Hence, corrosive degradation of combustor parts, vanes, and blades in gas turbines must be prevented. One of the most severe forms of corrosion is alkali‐sulfate‐induced hot corrosion, which is associated with internal sulfidation of components and is usually anticipated to fade in importance in the absence of sulfur. However, the literature suggests that hot corrosion might still occur in low‐sulfur combustion gases. In this study, established thermodynamic modeling methods are used to analyze the low‐sulfur hot corrosion regime. Liquid sodium chromate is found to be stable in these conditions. A comparison of calculation results and engine findings suggests that high alkali levels can negatively impact thermal barrier coating life even if sulfur is absent in the fuel. Laboratory tests are carried out to validate the chromate formation on MCrAlY‐coated specimens. It is shown that molten sodium chromate can alter the oxidation behavior of MCrAlY, promoting the formation of voluminous spinel. This represents a new and different form of hot corrosion compared to type I hot corrosion. Corrosive degradation of combustor parts, vanes, and blades in gas turbines diminishes the reliability of gas turbines and must be prevented. A sound understanding of conditions enabling corrosion is required. Hot corrosion—caused by alkali sulfates—is commonly assumed to be less critical in low‐sulfur environments, but the literature suggests that corrosion may still be present. The low‐sulfur hot corrosion regime is discussed in this study.